Prevalence of Malocclusion and Evaluation of Orthodontic Treatment Need amongst Patients in Pokhara, Nepal - Parajuli, Umesh; Tuladhar, Sapna Laxmi; Bajracharya, Manish; Pandey, Manju (Orthodontic Journal of Nepal, 2018)
Introduction: Prevalence of malocclusion and orthodontic treatment need varies according to different region based on ethnic diversity. Objective: To assess the prevalence of malocclusion and orthodontic treatment need amongst patients visiting College of Dental Surgery, Gandaki Medical College, Pokhara, Nepal. Materials & Method: A cross-sectional study based on WHO-Oral Health Survey Basic Methods using Community Periodontal Index (CPI) probe and mouth mirror was conducted. The malocclusion based on Angle’s classification, overjet, overbite, open bite, crowding, spacing and cross bites were recorded. Dental Health Components (DHC) of Index of Orthodontic Treatment Need (IOTN) was recorded. The frequency distribution was calculated and chi square test was used to assess the gender difference. Result: The prevalence of normal occlusion was 5.8%, Angle’s Class I malocclusion was 67.9%, Class II was 19.5% and Class III was 6.8%. Crowding (51.07%) was more common malocclusion trait than spacing (24.46%). There were no significant differences in distribution of various occlusal traits between male and female subjects. Orthodontic treatment need based on DHC showed: 19.40% were in definite/extreme need of treatment (Grade 4/5), 21.93% had borderline need (Grade 3) and 58.67% had no/ little need of treatment (Grade 1/2). Conclusion: Angle’s Class I was the most common malocclusion trait (67.9%) followed by anterior crowding (51.07%). 19.40% patients visiting the teaching hospital in Pokhara are in definite or extreme need of orthodontic treatment